Comparison of Simultaneous Prompting to Error Correction for Children With Autism Spectrum Disorder. (June 2022) - Aljohani, Wafa A.; Javed, Asim; Ferguson, Julia L.; Cihon, Joseph H.; Milne, Christine M.; Leaf, Justin B.
This study compared simultaneous prompting with an error correction procedure for teaching three children diagnosed with autism spectrum disorder expressive labels. Using a parallel treatment design nested within a multiple probe design, the researchers taught each participant how to expressively label pictures of sports teams or cartoon characters using either simultaneous prompting or an error correction procedure. The goal was to evaluate the effectiveness, efficiency, and acquisition during teaching for each participant across the two conditions. Results indicated that both teaching procedures were effective, with high rates of maintenance, and all participants responded correctly during the majority of teaching trials.